The Role of the Endocardium in the Origin of Dilated Cardiomyopathy(DCM) Structural Study Using by Scanning Electron Microscopic Investigation - Sheila Fatehpur; Michael Schultz; Peter Schwartz; Masoud Mirzaie (New Horizons in Medicine and Medical Research Vol. 9, 2022)
This study aimed to investigate the pathophysiological origin of Dilated cardiomyopathy (DCM) from a morphological point of view. To examine the anatomy of the endocardium, scanning electron and polarised light microscopy investigations were performed on explanted hearts from DCM patients. Four male (average age 72.21 years) and two female DCM patients had tissue samples obtained (63.14years). Patients with DCM who were on transplant waiting lists and were clinically characterized as stage NYHA III-IV were included in the study. The hearts of patients were removed for cardiac transplantation, and the explanted hearts were studied using scanning electron microscopy and polarised light microscopy. The basement membrane was largely desquamated from the endocardial layer, revealing isolated island-like cell structures. Areas of loosened cells connected to each other and to the basement membrane, abrasion of the endothelial cells, formation of filiform and lamellar Lambl’s excrescences, locally well-defined elevations above the intact endothelium, calcium deposits and hyperplasia of collagen fibers were detected. There were also micelle-like forms.